Answer: 18j -60 Step-by-step explanation: [tex]8(j-6) +2 (5j-6)\\\\\mathrm{Expand}\:8\left(j-6\right):\quad 8j-48\\\\=8j-48+2\left(5j-6\right)\\\\\mathrm{Expand}\:2\left(5j-6\right):\quad 10j-12\\\\=8j-48+10j-12\\\\\mathrm{Simplify}\:8j-48+10j-12:\\\quad 18j-60[/tex] Log in to Reply

Answer:## 18j -60

Step-by-step explanation:[tex]8(j-6) +2 (5j-6)\\\\\mathrm{Expand}\:8\left(j-6\right):\quad 8j-48\\\\=8j-48+2\left(5j-6\right)\\\\\mathrm{Expand}\:2\left(5j-6\right):\quad 10j-12\\\\=8j-48+10j-12\\\\\mathrm{Simplify}\:8j-48+10j-12:\\\quad 18j-60[/tex]